Pengaruh Kecerdasan Sepiritual dan Budaya Organisasi terhadap Kinerja Karyawan dengan Motivasi Kerja Sebagai Variabel Pemediasi di UD. Zaghal Pacitan - Sutri Aditya Yoga Kumbara; Agus Suyatno; Indra Hastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine whether Spiritual Intelligence can affect Employee Performance, Organizational Culture can affect Employee Performance, and Motivation can be a mediating variable between Organizational culture and Spiritual Intelligence on Employee Performance. This study uses a quantitative approach with data collection through questionnaires. With respondents as many as 50 employees at Ud. Zaghal Pacitan, East Java with 2 types of Permanent and Daily job groups. The results showed that spiritual intelligence can affect employee performance, organizational culture can affect employee performance, and motivation variables can be mediating variables between spiritual intelligence and organizational culture on employee performance.